(untitled) (Studia theodisca, 2025)
After 1801, Hölderlin’s poetry changed considerably through the reworking of earlier poems and the development of a major new project which would, however, remain fragmentary. Hölderlin experienced the political and military failure of revolution in his time . From his perspective, the spirit is filled with what most people ‘hope for’, but also what they do not expect: «Nicht daß irgend eine Form, irgend eine Meinung und Behauptung siegen wird […]». The modern world (hesperischer Orbis) and the current revolution have given rise to great change, even destruction, but also created new relationships and possibilities that have yet to be understood and expressed. Hölderlin explores the ambivalence of this new world both in the extensive fragments of Das Nächste Beste and in the perfectly accomplished poem Andenken. The poetic rhythm of memory resonates with that ambivalence and, at the same time, leads to the revelation of the forgotten origin of all things (das Ursprüngliche). The enduring realisation of the «vaterländische Umkehr» can only be achieved through the intimate appropriation of this rhythm.